A case series of subconjunctival triamcinolone acetonide injection for the treatment of upper eyelid retraction in thyroid eye disease - Chanh, Nhuien Tkhi Lin; Hien, Nguyen Thi Thu; Tung, Hoang Thanh; Anh, Vu Thi Que (Tạp chí Nghiên cứu Y học, 2026)
This study aimed to descriptively assess changes in eyelid position, disease activity, and ocular surface parameters following subconjunctival triamcinolone acetonide (80 mg/2 mL) injection in patients with upper eyelid retraction associated with thyroid eye disease. A case series was conducted on patients treated at Hanoi Medical University Hospital from October 2024 to October 2025. A total of 10 patients and 13 eyes were analyzed; 70.0% of patients had unilateral involvement, while 30.0% presented with bilateral disease. All patients were in a euthyroid state and were maintained on Thyrozol 5-10 mg/day. The mean number of injections was 1.8 ± 0.79. The mean CAS decreased from 2.00 ± 0.89 to 1.36 ± 1.02, and the mean MRD1 decreased from 6.99 ± 1.92 mm to 4.32 ± 1.18 mm following treatment. Favorable clinical outcomes were achieved in 70.0% of patients, 20.0% demonstrated moderate improvement, and 10.0% did not reach the expected therapeutic response. Disease duration and pre-injection severity of eyelid retraction were associated with treatment outcomes. There was no complication reported, except for one case of subcutaneous drug deposition, which resolved spontaneously within one month of follow-up.